KONSEP PERJODOHAN PERSPEKTIF PENGASUH PESANTREN SAYYID MUHAMMAD ALWI AL MALIKI DAN IMPLIKASINYA TERHADAP PEMBENTUKAN KELUARGA SAKINAH - Juhariyanto, Muhammad (Program Studi Hukum Keluarga Islam, 2023)
Matchmaking is often a conversation among teenagers at this time, which basically is an effort from the guardian to his child in determining a partner or a marriage that is not based on the independent efforts of the bride and groom to get married. This research is an Empirical Qualitative research that goes directly to the field to get data directly from the object of research (field research). By using descriptive-analytical method, strengthened by data documentation (secondary data) in the form of books, journals, previous research and yellow book literature, Al Quran, and Hadith. The subjects of this research are the caregiver of the pesantren and several alumni of Sayyid Muhammad Alwi Al maliki Islamic Boarding School and their alumni who were married based on matchmaking considerations made by the kiai and also several students who have been matched by the kiai based on his considerations.